Contextual Learning Model Based on Local Wisdom to Stimulate Early Childhood Social Skills - Yusuf, Syahran; Aula, Iqbal Ahsanul; Kahfi, Nazih Sadatul (LPPM Undiksha, 2025)
Social skills in early childhood are crucial to character building, school readiness, and long-term success in social life. However, many early childhood education institutions still emphasize academic-oriented learning, thus suboptimally stimulating children's social and emotional development. This study aims to design and test a contextual learning model based on the local wisdom of Kato Nan Ampek to improve children's social skills. The study used a Research and Development approach with the ADDIE model, involving experts, teachers, and children as subjects. Data were collected through observation, interviews, and expert validation. Data were analyzed using a combination of quantitative and qualitative descriptive techniques. The validation results showed that all learning tools were valid to very valid. The practicality test by teachers obtained an average score of 85.08%, indicating that this model is practical and easy to implement. The effectiveness test showed significant improvements in children's verbal communication, nonverbal communication, empathy, cooperation, and social problem-solving. These findings emphasize the importance of integrating local cultural values ​​into the early childhood education curriculum to strengthen social competence and support culturally responsive pedagogy.